2011
DOI: 10.1021/jf104432r
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Flavonoids and Nonphenolic Pigments during On-Tree Maturation and Postharvest Pericarp Browning of Litchi (Litchi chinensis Sonn.) As Shown by HPLC-MSn

Abstract: Polyphenols, chlorophylls, and carotenoids were characterized by HPLC-DAD-MS(n) in the pericarp of unripe to over-ripe 'Hong Huey' and 'Chacapat' litchi fruit at harvest and during subsequent storage (5 °C, 90% RH, 21 days). (-)-Epicatechin and A-type procyanidins always predominated quantitatively. Besides these ortho-diphenolic compounds, minor novel litchi flavonoids included monohydroxylated structures. Chlorophyll degradation by 73-92% and 7-38-fold anthocyanin accumulation affected pericarp color through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…Therefore, it was selected for evaluation of the effect of the combination of steam blanching and drying methods on the individual procyanidin profiles as shown in Table 2. The procyanidin A2 and epicatechin were the major procyanidins, which was in agreement with previous literature [16,17].…”
Section: Resultssupporting
confidence: 93%
“…Therefore, it was selected for evaluation of the effect of the combination of steam blanching and drying methods on the individual procyanidin profiles as shown in Table 2. The procyanidin A2 and epicatechin were the major procyanidins, which was in agreement with previous literature [16,17].…”
Section: Resultssupporting
confidence: 93%
“…The colors of the peppercorns are dependent on the chlorophyll content and various phytochemicals, which affect the flavonoid and phenolic contents and therefore, the antioxidant capacity. The contents of flavonoids and nonphenolic pigments are affected by the degree of the pepper fruit maturation and postharvest processing [39]. Our chromaticity analysis results showed that green pepper had high Hunter L* and b* values and low a* values, while black pepper had low Hunter L* and b* values and high a* values.…”
Section: Discussionmentioning
confidence: 72%
“…Storage of untreated samples did not modify the flavonoid profile of cashew apple pieces and this effect was similar to that observed on total polyphenols and phenolic acids (Figure 2a). The content of quercetin and kaempferol glycosides also remained stable in litchi fruits stored at 5℃ for 21 days (Reichel et al, 2011). Piljac-Zegarac and Samec (2011) evaluated total flavonoids in strawberry, raspberry, cherry, and gooseberry stored at 4 or 25℃ for 30 days and observed no changes in strawberry and cherry, while in raspberry and gooseberry it was observed reduction until 24% of initial levels.…”
Section: Flavonoidsmentioning
confidence: 99%